The Prevalence of Infection with Scabies, Yellow Fever and Myiasis in Some Ruminants in Thi-Qar Governorate During 2017 - Sadek J.T. (Journal of Global Pharma Technology, 2018)
The infection of external parasites is a common disease between humans and animals. Therefore, the current study aimed to investigate the prevalence of scabies disease as a disease caused by an external parasite is the mites as well as the study of other important diseases caused by viruses and Insecta such as yellow fever and myiasis. 40825 sheep, 940 cow and 2285 buffalo were examined and the infected animals were diagnosed in the laboratories of the veterinary hospital in Thi-qar governorate for the period from January to October 2017. The incidence of scabies in sheep, cows and buffalo were 65.03%, 53.64% and 38.03% respectively. The incidence of yellow fever in sheep, cow and buffaloes was 50.81%, 55.25% and 44.67% respectively. There were also significant differences between infection percentage according months of year. The incidence of myiasis among sheep, cow and buffaloes was 94.30%, 70.43%, and 70.95% respectively with significant differences between infection according months of year for all animals examined.Keywords: Infectious animals, External parasite, Scabies, Yellow Fever, Myiasis.